Biofunctional Characterization of Collagen from Orange-Spotted Grouper, Epinephelus coioides: Maintenance of Cartilage in Aged Zebrafish - Shao-Yang Hu; Chen-Han Tsou; Chung-Chih Tseng; Tai-Wei Han; Chun-Hung Liu (Fishes)
In this investigation, collagen was successfully extracted from the skin and fins of the orange-spotted grouper, Epinephelus coioides, with recovery rates of 4.45% and 23.65% (dry weight basis), respectively. UV–Vis spectrophotometric analysis demonstrated distinct absorbance peaks at 222 nm and 217 nm for collagen isolated from the skin and fins, correspondingly. Both collagen sources were confirmed to be type I, characterized by the presence of two α-chains (α1 and α2), with glycine as the predominant amino acid, an absence of tryptophan, and a notable content of proline and hydroxyproline. The enzymatic hydrolysis of fin-derived collagen using pepsin yielded low-molecular-weight peptides (PHC), which were subsequently incorporated into the diet of 1.5-year-old zebrafish, either alone or in combination with glucosamine (GC), to assess their biological effects. After eight weeks of dietary supplementation, zebrafish fed PHC or the combined PHC + GC diets exhibited a significant upregulation of sox9a (jef) expression in spinal tissues, accompanied by a marked downregulation of runx2. Although the differences in swimming performance among the groups were not statistically significant, zebrafish that received PHC or the combined supplements demonstrated enhanced endurance compared to the control group. These results suggest that collagen sourced from grouper may have advantageous effects in supporting cartilage health in aged zebrafish. Furthermore, utilizing fish by-products for collagen extraction enhances resource efficiency and aligns with circular economy principles.